2003
DOI: 10.1034/j.1600-048x.2003.03079.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of wind, season and latitude on the migration speed of white storks Ciconia ciconia, along the eastern migration route

Abstract: The relation between wind, latitude and daily migration speed along the entire migration route of white storks was analysed. Mean daily migration speed was calculated using satellite telemetry data for autumn and spring migration of white storks from their breeding grounds in Germany and Poland to wintering grounds in Africa and back. The National Center for Environmental Prediction (NCEP) reanalysis data were used to systematically fit 850 mb wind vectors to daily migration speed along the migration route. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(121 citation statements)
references
References 17 publications
5
106
0
3
Order By: Relevance
“…Accordingly, the time thus spent flying over both continents was comparable, despite a much longer distance travelled over Africa than in Europe. In the same way, maximum flight speeds (km h 21 ) for all individuals were accomplished on the African continent, and there was a net decrease in the mean daily distance of black storks north of latitude 358 N. A higher migration speed in Africa compared with Europe has also been reported for white storks using the eastern migration route (Shamoun-Baranes et al 2003b). Moreover, we found a coincidence of pattern in black storks, on a daily time scale, between the distribution of thermal convection and the windows of migratory activities.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Accordingly, the time thus spent flying over both continents was comparable, despite a much longer distance travelled over Africa than in Europe. In the same way, maximum flight speeds (km h 21 ) for all individuals were accomplished on the African continent, and there was a net decrease in the mean daily distance of black storks north of latitude 358 N. A higher migration speed in Africa compared with Europe has also been reported for white storks using the eastern migration route (Shamoun-Baranes et al 2003b). Moreover, we found a coincidence of pattern in black storks, on a daily time scale, between the distribution of thermal convection and the windows of migratory activities.…”
Section: Discussionmentioning
confidence: 65%
“…In this species, Shamoun-Baranes et al (2003b) reported longer daily distances in autumn compared with spring owing to dominant autumnal tailwinds. The second factor known to affect the characteristics of migration of soaring birds is the prevalence of thermal convection (Leshem & YomTov 1996;Liechti et al 1996;Shamoun-Baranes et al 2003a,c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The European white stork breeding population was recently estimated at 180,000 -220,000 breeding pairs (Burfield and Bommel, 2004). The majority of these birds migrate to spend the winter in the Sahel and East and South Africa Berthold et al, 2002) migrating on average 250 km/d (Berthold et al, 2000;Shamoun-Baranes et al, 2003b). White storks are diurnal flocking migrants relying on thermal convection and thus most birds migrate either east or west of the Mediterranean to avoid crossing long stretches of the Mediterranean Sea, converging in Israel and Gibraltar respectively.…”
Section: White Stork Migrationmentioning
confidence: 99%
“…In the white stork, the timing of departure for spring migration and its duration is highly dependent on the weather conditions (Shamoun-Baranes et al 2003;Berthold et al 2004). In consequence, white storks show great within-population variability in the timing of arrival at breeding areas, with the last individuals arriving no earlier than in mid-May to Central Europe (Janiszewski et al 2013).…”
Section: Discussionmentioning
confidence: 99%